2022
DOI: 10.1001/jamanetworkopen.2022.31937
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Emergency Department Visits for Cannabis Hyperemesis Syndrome Following Recreational Cannabis Legalization and Subsequent Commercialization in Ontario, Canada

Abstract: IMPORTANCE Prior research suggests that the legalization of recreational cannabis is associated with increases in cannabis hyperemesis syndrome (CHS), but it is unclear how cannabis commercialization (ie, greater retail store access as well as increased variety and potency of cannabis products) may be associated with these changes.OBJECTIVES To examine changes in the number and characteristics of CHS emergency department (ED) visits from before to after legalization of cannabis in Ontario, Canada. DESIGN, SETT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…While the implications of this variation are relatively unknown, a large body of literature from alcohol control [5] caution that it may result in differences in use and consequent harms. Increasing research from Canada and the United States has found that greater retail access to cannabis stores is associated with increases in cannabis use and health care visits caused by cannabis across several populations [6,7,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the implications of this variation are relatively unknown, a large body of literature from alcohol control [5] caution that it may result in differences in use and consequent harms. Increasing research from Canada and the United States has found that greater retail access to cannabis stores is associated with increases in cannabis use and health care visits caused by cannabis across several populations [6,7,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Canadian evidence suggests minimal changes in cannabis use and consequent health care visits immediately following legalisation [5]. More recent studies suggest that cannabis use and health care visits may be increasing as the market has expanded including the phased introduction of new higher-potency products such as vapes, edibles and concentrates, which began 1 year post legalisation in October 2019 [6][7][8][9]. However, there are no published data on how retail store access has changed in Canada in years 3 and 4 following legalisation.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, while we believe that the Canadian experience regarding legalization will generalize to other countries, we highlight that legalization itself can take multiple forms. Our ongoing research suggests that regulatory decisions such as allowing or restricting cannabis marketing and promotion, retail access, product types and cannabis potency can all influence cannabis use and related health outcomes post-legalization [10][11][12][13]. Consequently, as other countries proceed towards legalization, we caution that policies that allow higher levels of commercial access risk important population-level changes in cannabis use and consequent harms.…”
Section: Response To Smyth and Mccarron: Increases In Cannabisattribu...mentioning
confidence: 98%
“…associated with any changes in rates of emergency admissions. 80 As this attenuation occurred in Canada prior to commercialization where strict purchasing policy was in place, it may suggest that having proper regulations in place can prevent the uptick in cannabis-related emergency visits seen in U.S. studies. Other hospital-related outcomes examined included admissions for cannabis misuse and other substance use exposure.…”
Section: Table 3 (Continued)mentioning
confidence: 99%